Peran PLKB (Petugas Lapangan Keluarga Berencana) Dalam Program Percepatan Penurunan Angka Stunting Di Desa Kramat Kecamatan Kota Kudus Kabupaten Kudus Tahun 2024 - Fadhila Rania Rakhmadanti; Ruhadi (Universitas Negeri Semarang, 2025)
Stunting is one of the serious problems in human resource development in Indonesia. This condition is characterized by growth disorders in childern due to chronic malnutrition that lasts for a long time. The Indonesian government has issued Presidential Regulation No. 72 of 2021 on Accelerating The Reduction of stunting, in which Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) serve as the main coordinator. This study aims to determine the role of Pelaksana Lapangan Keluarga Berencana (PLKB) in the program to accelerate the reduction of stunting rates in Kramat Village, Kudus District, as well as to identify the obstacles faced in the implementation of the program. The method used in qualitative with an institutionalist approach. Data sources include primary and secondary sources, with data collection tchniques involving interviews, observations, and documentation. Validation techniques included source triangulation and technique triangulation. Data analysis involved data reduction, data presentation, and conclusions. The research findings indicate that PLKB play a crucial rolr as intermediaries between institutions, implementers of socialization and education, implementers of accompaniment, and field monitors. However, challenges include budget conctraints, lack of community understanding, and technical difficulties in the field. Enhanced cross-sectoral collaboration and reguler training for cadres are needed to strengthen efforts to accelerate the reduction of stunting.